A ORIGEM DO CONCEITO DE CLASSIFICAÇÃO E SUA APLICABILIDADE NOS DOCUMENTOS DE ARQUIVO - Fernanda Maria de Andrade Ferreira (LexCult, 2019)
The purpose of this paper is to search for the origin and development of the construction of the classification plans and how they were established in the literature and archival thinking. The focus is on identifying how, from the origin of classification, document management was built to a knowledge of archival documents. It also seeks to recognize the principles of respect for funds and the original order as precious foundations for archival classification. The attempt is to identify the genesis of this discipline and the repercussions of its practice.